IMPLEMENTASI SUPERVISI AKADEMIK KEPALA MADRASAH DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU DI SEKOLAH DASAR NEGERI GUGUS GINTUNG - Hentriani, Yati (UNISAN JURNAL, 2025)
This study aims to describe the implementation of academic supervision by the head of the madrasah in improving teachers’ pedagogical competence at the Gintung Cluster State Elementary School. This research employed a qualitative descriptive approach using interviews, observations, and documentation techniques. The findings reveal that the supervision program was prepared at the beginning of each academic year; however, it was not based on a comprehensive needs analysis and did not fully involve teachers. The supervision was carried out through classroom observations and individual coaching, but it remained traditional and lacked deep reflective feedback. The follow-up of supervision was inconsistent, resulting in less optimal improvement in teachers’ pedagogical competence, particularly in lesson planning, active teaching methods, instructional media, and authentic assessment. This study highlights the importance of collaborative, structured, and continuous academic supervision to enhance teacher professionalism and instructional quality.